Analysis of Marketing Strategy in Increasing Sales Volume in the Onion Cracker Industry (Case Study of UMKM XYZ) - Syifa Safira Parameshwari; Dene Herwanto; Risma Fitriani (Tibuana, 2023)
A marketing strategy is a plan used by business actors in marketing a product so that the product can compete in an increasingly tight business world. UMKM XYZ is one of the business actors in the cracker industry in the city of Bekasi. UMKM XZY in the last year experienced a decline in sales levels. This was due to the lack of marketing strategies in marketing their products that could increase sales volume. This study aims to determine the marketing strategy to increase sales volume at UMKM XYZ. The marketing mix is one of the factors that can affect sales volume, the elements in the Marketing Mix are product, price, place, and promotion. This study uses qualitative research methods to examine more deeply the product, price, place, and promotion strategies in increasing the sales volume of UMKM XYZ. Data collection techniques using direct interviews and observation. This study concludes that the marketing strategy that UMKM XYZ in increasing sales volume can do is to innovate products, expand the target market, and increase promotional activities using social media.